Ikan Zebra (Danio rerio) sebagai Binatang Model pada Penelitian Biomedis dan Cara Pemeliharaannya - Husnul Khotimah; M. Muljohadi Al (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2020)
Biomedical research requires suitable model organisms to be able to understand the pathogenesis of disease at the cellular and molecular level and the suitability of systems for the development and testing of new therapies. The choice of model organisms for biomedical research depends very much on the research objectives. Basically, the selection of model organisms is based on several aspects, namely: biological, technical and historical aspects. The general criteria for selecting model organisms are: small size, fast reproduction time, low and easy maintenance, easy experimental techniques, complete basic information. The development of research using animal models further leads to the level of genetic functional conservation in the basic processes of cell biology between mammals and invertebrates such as fruit flies (Drosophila melanogaster) and nematode worms (Caenorhabditis elegans). However, there are significant limitations between mammals and invertebrates, among others due to differences in organ systems and their development, so now widely used zebra fish (Danio rerio) as model organisms that bridge between invertebrates and vertebrates. In addition to these reasons there are several other scientific reasons that make zebra fish a superior organism model for biomedical research, namely: having a high homology with humans (75%), transparent embryos, high levels of fecundity, fast embryogenesis, relatively fast life span , procurement and maintenance is relatively inexpensive, complete basic information and genetic information (whole genome sequencing), has a cardiovascular system, nerves, immune system and digestive system similar to mammals, sensitive to environmental changes so that many bio-indicators are used for toxicity testing and testing and development drug.